Roman Property Law in the Comparative Analysis of the Institutes of Gaius and Institutes of Justinian - Stojanović, Stefan V. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
The paper compares the provisions of Roman property law in Institutes of Gaius and Institutes of Justinian. The aim of the paper is to find out which provisions of the Institutes of Gaius were recieved in Institutes of Justinian, and which were not, and whether certain provisions were taken with modification and what the modification consists of. In this way it will be determined which institutes of Roman property law remained unchanged until Justinian's time, which underwent changes, and which, due to changes in social relations ceased to exist. Through the comparative method, an analysis of the most important legal concepts and institutes of Roman property law in the Institutes, will be carried out.